A Nine Case Series of Ultrasound-Guided Hydrostatic Reduction of Intussusception by Saline Enema - Limchareon, Sornsupha; Boonyarit, Adisorn (The ASEAN Journal of Radiology, 2013)
Non-surgical reduction of the intussusception is the first line treatment in children with intussusception. Among various radiological reduction techniques, barium enema reduction of the intussusception under fluoroscopy has been widely used in Thailand while pneumatic reduction under fluoroscopy has become popular in teaching hospitals. To our knowledge, ultrasound-guided hydrostatic reduction of the intussusception by saline enema (UGHSE) has never been used in Thailand. We reported 9 cases using UGHSE with 100% success rate without complication.